Β-Carotene bioaccessibility from biofortified maize (Zea mays) is related to its density and is negatively influenced by lutein and zeaxanthin. Issue 1 (7th December 2017) - Dube, Nivedita; Mashurabad, Purna Chandra; Hossain, Firoz; Pullakhandam, Raghu; Thingnganing, Longvah; Bharatraj, Dinesh Kumar
Abstract : The β-Carotene bioaccessibility is higher from biofortified maize and is negatively influenced by lutein and zeaxanthin. Abstract : Biofortification of maize with provitamin A (pro-VA) carotenoids has been successful, but the bioavailability of carotenoids needs to be explored. In the present study, we investigated the carotenoid content, micellarization and intestinal cell uptake of carotenoids from 10 maize hybrids [normal maize, quality protein maize (QPM), pro-VA carotenoid and double biofortified QPM + pro-VA maize hybrids] using a simulated in vitro digestion/Caco-2 cell model. The pro-VA carotenoid content of biofortified maize hybrids is 2–10 fold higher compared to that of normal maize. Furthermore, the ratio of non-pro-VA carotenoids lutein (LUT) plus zeaxanthin (ZEA) to the sum of pro-VA carotenoids β-cryptoxanthin (BCX), α-carotene (AC) and β-carotene (BC) in biofortified maize was much lower compared to that of normal maize. The consumption of 200 g day −1 of biofortified Pusa-PV-16-3 (BC = 808.4 μg per 100 g; AC = 839.3 μg per 100 g; BCX = 59 μg per 100 g) and Pusa-APQH8 (BC = 345.9 μg per 100 g; AC = 1739 μg per 100 g; BCX = 644.2 μg per 100 g) maize would contribute to 52 and 64% of RDAs for adult Indian men, respectively, after adjusting for cooking losses and conversion factors. The mean efficiency of micellarization of LUT (62.2% ± 5.3), ZEA (65% ± 4.7), and BCX (54% ± 9.5) exceeded that of AC (43% ± 8.9) and BC (49.8% ± 7.8) from all the maize hybrids. Furthermore, the micellarization and uptake in Caco-2 cells during a 4 h incubation period showed high correlation ( P < 0.05) with the concentration of carotenoids in the maize digesta and micellar fraction, respectively. However, the LUT + ZEA content in the maize digesta and micellar fraction was inversely ( p < 0.05) related to the BC micellarization and intestinal cell uptake, respectively. These results together suggest that the enrichment of pro-VA carotenoids together with decreasing the oxygenated carotenoid metabolites such as LUT and ZEA will further improve the bioavailability of BC from maize hybrids.